How Aspects of Characteristic-Based Learner Development: Cognitive, Affective, and Psychomotor Aspects - Wahyuddin Naro; Mirnawati Mirnawati; Suarni Suarni; Sitti Maryam Gani (South Sulawesi Education Development (SSED), 2023)
The aspects of characteristic-based learner development are three dimensions that must be considered during the learner development process.The three dimensions are: 1) The cognitive aspect, which includes the development of thinking, reasoning, and understanding skills. This aspect aims to develop learners' abilities to process information and solve problems. 2) Affective aspects, which include the development of one's feelings, attitudes, and emotions. This aspect aims to develop learners' abilities to control and manage their emotions and form a positive attitude towards themselves and others. 3) Psychomotor aspects, which include the development of a person's physical abilities, including muscle coordination, speed, and strength. This aspect aims to develop learners' abilities to perform various physical activities, such as sports, arts, and work. The development of these three aspects is necessary so that learners can become physically and mentally healthy individuals and be able to adjust to their environment.